SAT0243 Incidence of thromboembolic events in the tofacitinib rheumatoid arthritis, psoriasis, psoriatic arthritis and ulcerative colitis development programmes. (12th June 2018) - Mease, P.J.; Kremer, J.; Cohen, S.; Curtis, J.R.; Charles-Schoeman, C.; Loftus, E.V.; Greenberg, J.; Palmetto, N.; Kanik, K. S.; Graham, D.; Wang, C.; Biswas, P.; et al.
Abstract : Background: Tofacitinib is an oral Janus kinase (JAK) inhibitor that preferentially inhibits signalling by JAK3 and JAK1, with functional selectivity over JAK2. Potential increased risk of venous thromboembolic events (VTE) in patients (pts) with rheumatoid arthritis (RA) has been reported for a JAK 1/2 inhibitor. 1 Objectives: To assess VTE risk with tofacitinib in pts with RA, psoriasis (PsO), psoriatic arthritis (PsA) and ulcerative colitis (UC). Methods: Data from Phase (P)2 (RA, PsO, UC) and P3 (RA, PsO, PsA, UC) randomised clinical studies of tofacitinib as monotherapy or in combination with conventional synthetic (cs)DMARDs were reviewed. Two cohorts were defined; 1) the placebo (PBO)-controlled cohort: pts randomised to tofacitinib 5 or 10 mg BID, or PBO up to Month (M)3 in RA, PsO and PsA studies, and pts randomised to tofacitinib 10 mg BID or PBO for the 9-week induction period in UC studies; 2) the dose-comparison cohort: pts randomised to tofacitinib 5 or 10 mg BID, adalimumab (ADA) 40 mg SC Q2W (RA and PsA only) or methotrexate (MTX) 20 mg QW (RA only) throughout the P2/3 studies for RA (up to M24), PsO (up to M12) and PsA (up to M12), and for the 12-month P3 UC maintenance study. First deep vein thrombosis (DVT) and pulmonary embolism (PE) events were identified using the MedDRA embolic and thrombotic SMQ preferred terms restricted to the respiratory, thoracic, mediastinal and vascular disorder System Organ Classes; incidence rates (IRs; pts with events/100 pt-years) were based on single events occurring during treatment or ≤28 days after the last dose or up to the cohort cut-off date. IRs for PE in RA pts were compared with Corrona Registry data (May 2017 cut-off). Results: Up to M3 in the PBO-controlled cohort, DVT and PE each occurred in 2 pts receiving PBO (1 RA pt and 1 UC pt per event); no tofacitinib-treated pts had DVT or PE events (Table). In the dose-comparison cohort 2 DVT events occurred in tofacitinib-treated pts with RA (5 mg BID, n=1; 10 mg BID, n=1) and 1 DVT event in a pt with PsA (tofacitinib 10 mg BID) (Table). IRs (95% CI) were 0.1 (0.0, 0.3) for both tofacitinib doses in RA and 0.5 (0.0, 2.8) for tofacitinib 10 mg BID in PsA. Two DVT events occurred with MTX; none with ADA. Five PE events occurred in the dose comparison cohort, all in RA (5 mg BID, n=2; 10 mg BID, n=3). IRs were 0.1 (0.0, 0.4) for tofacitinib 5 mg BID and 0.2 (0.0, 0.4) for 10 mg BID. IRs for PE with tofacitinib in RA were similar to those reported by the Corrona Registry in RA pts treated with tofacitinib (0.1 [0.0, 0.4]), biologic DMARDs (0.2 [0.1, 0.3]) and csDMARDs (0.2 [0.0, 0.5]). Conclusions: Analysis of DVT and PE across randomised clinical studies for RA, PsO, PsA and UC showed no evidence of an increased risk of these events with tofacitinib vs other therapies. Reference: [1]Weinblatt M, et al. Arthritis Rheumatol2017;69(suppl 10):2352. Acknowledgements: Study sponsored by Pfizer Inc. Medical writing support was provided by A MacLachlan of CMC and funded by Pfizer Inc. Disclosure of Interest: P. Mease Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, Sun, UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, Sun, UCB, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Genentech, Janssen, Novartis, Pfizer Inc, UCB, J. Kremer Shareholder of: Corrona LLC, Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Eli Lilly, Genentech, Novartis, Pfizer Inc, Regeneron, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Eli Lilly, Genentech, Novartis, Pfizer Inc, Regeneron, Employee of: Corrona LLC, S. Cohen Grant/research support from: Pfizer Inc, Consultant for: AbbVie, Amgen, Boehringer Ingelheim, Gilead, Merck, Pfizer Inc, J. Curtis Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Corrona LLC, Crescendo Bio, Eli Lilly, Janssen, Myriad, Pfizer Inc, Roche, UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Corrona LLC, Crescendo Bio, Eli Lilly, Janssen, Myriad, Pfizer Inc, Roche, UCB, C. Charles-Schoeman Grant/research support from: AbbVie, Bristol-Myers Squibb, Pfizer Inc, Consultant for: Amgen, Gilead, Pfizer Inc, Regeneron-Sanofi, E. Loftus Jr Grant/research support from: AbbVie, Allergan, Amgen, Celgene, Celltrion, CVS Caremark, Eli Lilly, Genentech, Gilead, Janssen, MedImmune, Mesoblast, Napo Pharmaceuticals, Pfizer Inc, Receptos, Robarts Clinical Trials, Salix, Seres Therapeutics, Takeda, UCB, Consultant for: AbbVie, Allergan, Amgen, Celgene, Celltrion, CVS Caremark, Eli Lilly, Genentech, Gilead, Janssen, MedImmune, Mesoblast, Napo Pharmaceuticals, Pfizer Inc, Receptos, Robarts Clinical Trials, Salix, Seres Therapeutics, Takeda, UCB, J. Greenberg Consultant for: Eli Lilly, Genentech, Janssen, Novartis, Pfizer Inc, Employee of: Corrona LLC, N. Palmetto Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Kanik Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Graham Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, P. Biswas Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, G. Chan Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. DeMasi Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, H. Valdez Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Hendrikx Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Jones Shareholder of: Pfizer Inc, Employee of: Pfizer Inc